Relationship between inflation and inflation uncertainty: The case of Serbia - Mladenović, Z. (Yugoslav Journal of Operations Research; Vol 19 No 1 (2009): Vol. 19 No. 1, 2016)
The purpose of this paper is to examine the relationship between inflation and inflation uncertainty in the Serbian economy, being particularly vulnerable to shocks in inflation rate, during transition period 2001 - 2007. Based on monthly data several GARCH specifications are estimated to provide the measure for inflation uncertainty. Derived variables are then included into VAR model to test for Granger-causality between inflation and its uncertainty. Models that consider only permanent and transitory components of prices are also estimated to investigate the inflation-uncertainty relationship in the long and in the short run. The main conclusion of the paper is that high inflation invokes high uncertainty, while high uncertainty negatively affects the level of inflation at long horizon.